2010
DOI: 10.4995/wrs.2010.18.08
|View full text |Cite
|
Sign up to set email alerts
|

Diet digestibility in growing rabbits: effect of origin and oxidation level of dietary fat and vitamin e supplementation.

Abstract: ABSTRACT:The effects of the dietary inclusion of fats with different origin (lard or vegetal oil), fatty acid profi le (linseed or sunfl ower), oxidation level (fresh, peroxidised: 11 d at 55ºC or oxidised: 31 h at 140ºC) and vitamin E supplementation (0 or 100 ppm) on the rabbit diet apparent digestibility were studied. Digestibility coeffi cients of dry matter, organic matter, crude protein, ether extract and gross energy were determined in eight diets using 58 rabbits aged 49 d. Contrast analysis between gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…These results were expected because of the moderate amounts of dietary fat supplementation used in the present study (15 g/kg). Fernández et al (1994) and Casado et al (2010) using a greater amount (30 g/kg) of supplementation with different fat sources varying in the ratios of saturated/unsaturated FA did not observe any difference on nutrient digestibility in fattening rabbits. Nevertheless, Dalle Zotte et al (2013) observed a slight decrease of the apparent digestibility coefficient of ether extract in 11-week-old rabbits due to the increase of PUFA content (20 g/kg) in diets supplemented with Spirulina meal.…”
Section: Discussionmentioning
confidence: 81%
“…These results were expected because of the moderate amounts of dietary fat supplementation used in the present study (15 g/kg). Fernández et al (1994) and Casado et al (2010) using a greater amount (30 g/kg) of supplementation with different fat sources varying in the ratios of saturated/unsaturated FA did not observe any difference on nutrient digestibility in fattening rabbits. Nevertheless, Dalle Zotte et al (2013) observed a slight decrease of the apparent digestibility coefficient of ether extract in 11-week-old rabbits due to the increase of PUFA content (20 g/kg) in diets supplemented with Spirulina meal.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, relevant changes in digestive physiology occur around weaning when solid intake begins (17-18 d old) and diet has a great influence (Soler et al, 2005), although the effect of dietary fatty acids profile (Eiben et al, 2010) and oxidation level (Casado et al, 2011) seem to be moderate, and Casado et al (2010) found no differences in the digestibility coefficient between diets including different PUFA sources.…”
Section: Introductionmentioning
confidence: 89%
“…In the first study (fattening trial) a total of 1670 (585±4 g) weaned rabbits aged 28 d were randomly housed: 750 in individual cages (150 per treatment) and 920 in collective cages (184 per treatment; 8 rabbits/cage) and had free access to one of the experimental diets from 28 to 63 d of age. Daily weight gain (DWG) Casado et al (2010). World Rabbit Sci.…”
Section: Animal and Experimental Proceduresmentioning
confidence: 99%
“…The lipid oxidation degree of oil did not affect digestibility of nutrients in pigs (Derouchey et al, 2000) or rabbits Casado et al, 2010), and Zdunczyk et al (2000) described a lower fat digestibility only when high-oxidised fats (200 meq O 2 /kg and ρ-anisidine value of 96) were included at 10% in diet for rats, but not affecting feed intake and body weight gain. Effects of oxidised fats on animal performance also seem to be related with their oxidation degree and inclusion level.…”
Section: Introductionmentioning
confidence: 99%
“…The peroxidised (P) and highly oxidised (O) oils were obtained from fresh (F) sunflower oil (peroxide value of 10 meq O 2 /kg oil and ρ-anisidine value of 3) by 2 heat treatments (55°C for 11 d or 140°C for 31 h, respectively; see Casado et al, 2010) which increased the content of primary oxidation compounds (P oil), as was reflected in a peroxide value of 83 meq O 2 / kg oil without variation of ρ-anisidine value, or induced the formation of secondary oxidation compounds and polymerisation reactions (O oil), reaching a ρ-anisidine value of 125, 10% of polymerised triacylglycerols and 1.9 g/kg oil of total trans-fatty acids. Immediately after the heat treatments, butyl-hydroxytoluene was added to the oils at 100 mg/kg for their stabilisation, avoiding further oxidation.…”
Section: Experimental Oils and Dietsmentioning
confidence: 99%